Educational reading of Siberian and Far Eastern population in the late XX - early XXI centuries - Yu. V. Timofeeva (Библиосфера, 2017)
The article is devoted to reading modification, which is most widespread today, educational reading. For the first time educational reading of Siberian and Far Eastern residents became a subject of an independent research. Its importance to develop a personality, society, state is reasoned. The author considers the corpus making educational reading, to which refers textbooks, manuals, reference books, encyclopedias, fiction according to school curricula and other editions that addressing is related to educational activity. The audience of educational reading is revealed and characterized, its age and gender structure is defined. Children, teenagers, youth entered it by age criterion, mainly women by a gender one. Pupils made the most group of users of municipal and state libraries on number. Among them senior school children more often addressed to libraries for preparation to classes. Requests for educational literature averaged from 60 to 90% of all requirements in municipal libraries of the region. Author's definitions of the term «educational reading» are offered to a scientific community for discussion.